Analisis Pengajuan Soal Matematika Siswa Ditinjau dari Gaya Kognitif Visualizer dan Verbalizer - Luluk Chumairoh; Ana Rahmawati; Tafsillatul Mufida Asriningsih (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2022)
Problem posing in this research asks students to make questions. One of the internal factors that affect the ability of students in posing problems was student cognitive style. The purpose of this study, describe the student's mathematical problem posing in terms of the visualizer and verbalizer cognitive styles. This type of research was qualitative research. Research instruments were the VVQ (Visualizer and Verbalizer Questionnaire) test, problem-posing test, and interview guidelines. The results of this study were that the visualizer subject posed more problems from visual information than verbal information, all the problems made were categorized as assignment propositions, and only contained one semantic relation. Meanwhile, the verbalizer subject makes the number of questions the same between verbal and visual information, the problems made were categorized as assignment propositions and categorized as conditional propositions, and all problems contain only one semantic relation.